Incidental pigmented basal cell carcinoma discovered on positron emission tomography (PET) - Jazaeri, Yasaman; Del Marmol, Véronique; Suppa, Mariano; Dumarey, Nicolas (JEADV clinical practice, 2024)
Basal cell carcinoma (BCC), which frequently occurs in sun‐exposed areas of the head and neck region, is the most common cutaneous malignancy but the least studied with radiologic imaging techniques. This article outlines the case of a 65‐year‐old male with a pigmented BCC of the right shoulder discovered on positron emission tomography‐computed tomography (PET/CT). The lesion was initially suspected as a melanoma. However, the histopathological features showed a tumor of basaloid cells. PET/CT is an excellent technique for the detection of hypermetabolic tumors, such as melanoma, squamous cell and Merkel cell carcinomas, in lymph nodes and distant organs. The usefulness of PET is limited for slowly growing tumors, such as BCC. However, PET/CT can be useful for the detection of distant metastasis in locally advanced BCC as well as in the follow‐up of locally advanced BCC on Hedgehog inhibitors. This article outlines the case of a 65‐year‐old male with a pigmented basal cell carcinoma (BCC) of the right shoulder discovered on positron emission tomography‐computed tomography (PET/CT). BCC is the most common cutaneous malignancy but the least studied with radiologic imaging techniques. The usefulness of PET is limited for slowly growing tumors. However, PET/CT can be useful for the detection of distant metastasis in locally advanced BCC as well as in the follow‐up of locally advanced BCC on Hedgehog inhibitors.